2013
DOI: 10.1159/000356447
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Function in Human Diseases

Abstract: MicroRNAs are emerging as a hot topic in research, and rightfully so. They show great promise as targets of treatment and as markers for common human diseases, such as cancer and metabolic diseases. In this review, we address some of the basic questions regarding microRNA function in human disease and the clinical significance of microRNAs. Specifically, microRNAs in epigenetics, cancer, and metabolic diseases are discussed, with examples taken from cholangiocarcinoma and nonalcoholic fatty liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…Among these only four of them (miR-185, miR199a-3p, miR-214 and miR-490) were shown to be similarly altered in liver tissue and circulation [ 29 ]. This suggests that circulating microRNAs are not solely from liver damage; another major source of circulating microRNAs was blood cells [ 30 , 31 ]. A recent analysis of patients with diabetes showed that there was a difference in the levels of circulating microRNAs between platelet-rich plasma and platelet-poor plasma suggesting that platelets are substantial contributors of microRNA in the circulation [ 32 , 33 ].…”
Section: Circulating Micrornas In Aldmentioning
confidence: 99%
“…Among these only four of them (miR-185, miR199a-3p, miR-214 and miR-490) were shown to be similarly altered in liver tissue and circulation [ 29 ]. This suggests that circulating microRNAs are not solely from liver damage; another major source of circulating microRNAs was blood cells [ 30 , 31 ]. A recent analysis of patients with diabetes showed that there was a difference in the levels of circulating microRNAs between platelet-rich plasma and platelet-poor plasma suggesting that platelets are substantial contributors of microRNA in the circulation [ 32 , 33 ].…”
Section: Circulating Micrornas In Aldmentioning
confidence: 99%
“…During the past decades, several miRNAs have been described to modulate cholangiocyte proliferation, like let-7a, miR-21, -26a, -34a, -421, and -494. [62][63][64] Some recent reports reveal that miRNAs likely promote cell growth via regulation of receptor tyrosine kinase and MAPK signaling, particularly in CCA. One of these miRNAs, miR-376c, was found to be significantly downregulated in CCA cell lines compared with a normal bile duct epithelial cell line.…”
Section: Cholangiocyte Proliferationmentioning
confidence: 99%
“…As in other malignancies, microRNA dysregulation in CCA has been associated with the repression of tumor suppressor genes and the upregulation of oncogenes, affecting a myriad of cellular processes and phenotypes including proliferation, apoptosis and stress resistance, migration, invasion, and epithelial- mesenchymal transition (EMT). Indeed, multiple microRNAs are dysregulated in CCA [5, 6] and several have validated molecular targets (Table 1). Much of the recent work has focused on examining molecular targets and pathophysiological outcomes of altered microRNA expression.…”
Section: Cholangiocarcinomamentioning
confidence: 99%